2006
DOI: 10.1007/bf02708765
|View full text |Cite
|
Sign up to set email alerts
|

Design and fabrication of an automated temperature programmed reaction system to evaluate 3-way catalysts Ce1−x−y ,(La/Y) x Pt y O2−δ

Abstract: A completely automated temperature-programmed reaction (TPR) system for carrying out gas-solid catalytic reactions under atmospheric flow conditions is fabricated to study CO and hydrocarbon oxidation, and NO reduction. The system consists of an all-stainless steel UHV system, quadrupole mass spectrometer SX200 (VG Scientific), a tubular furnace and micro-reactor, a temperature controller, a versatile gas handling system, and a data acquisition and analysis system. The performance of the system has been tested… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
11
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 14 publications
1
11
0
Order By: Relevance
“…This confirms that Pt ions are substituted in the lattices of Ce 1− x Ti x O 2−δ and CeO 2 for Ce 4+ in catalysts II and III (Figure b,c). Substitution of Pt ion in Ce 1− x La x O 2−δ has also been reported earlier . Detailed studies on the structure of Ce 0.98 Pt 0.02 O 2−δ , Ce 0.83 Ti 0.15 Pt 0.02 O 2−δ , and Ce 0.78 La 0.20 Pt 0.02 O 2−δ by XRD, XPS, TEM, and EXAFS have shown that Pt ion is substituted for Ce 4+ ion and Pt 2+ is the major constituent (78%) in these compounds. ,,, …”
Section: Resultssupporting
confidence: 67%
“…This confirms that Pt ions are substituted in the lattices of Ce 1− x Ti x O 2−δ and CeO 2 for Ce 4+ in catalysts II and III (Figure b,c). Substitution of Pt ion in Ce 1− x La x O 2−δ has also been reported earlier . Detailed studies on the structure of Ce 0.98 Pt 0.02 O 2−δ , Ce 0.83 Ti 0.15 Pt 0.02 O 2−δ , and Ce 0.78 La 0.20 Pt 0.02 O 2−δ by XRD, XPS, TEM, and EXAFS have shown that Pt ion is substituted for Ce 4+ ion and Pt 2+ is the major constituent (78%) in these compounds. ,,, …”
Section: Resultssupporting
confidence: 67%
“…The catalytic test was done in a temperature-programmed reaction system described elsewhere . The catalyst (40/80 mesh) diluted with SiO 2 (30/60 mesh size) was loaded in the reactor to get a column length of 1.1 cm and the endings were plugged with ceramic wool.…”
Section: Methodsmentioning
confidence: 99%
“…However, the selectivity of N 2 and N 2 O was not measured. Further it was proved that the rate of the reaction increases with the increase in oxide ion vacancies by substituting La or Y in CeO 2 with Pt [69].…”
Section: No X Reduction By Comentioning
confidence: 98%